Hazardous Waste Cleanup, Neighborhood Gentrification, and Environmental Justice: Evidence from Restricted Access Census Block Data - Gamper-Rabindran, Shanti; Timmins, Christopher (American Economic Review, 2011)
We test for residential sorting and changes in neighborhood characteristics in response to the cleanup of hazardous waste sites using restricted access fine-geographical-resolution block data. We examine changes between 1990 and 2000 in blocks within 5km of sites that are proposed to the National Priority List that fall in a narrow interval of Hazardous Ranking Scores, comparing blocks near sites that were cleaned with those near sites that were not. Cleanup leads to increases in population density and housing unit density; increases in mean household income and shares of college-educated; but also to increases in the shares of minorities.